RNA Imaging with Dimeric Broccoli in Live Bacterial and Mammalian Cells - Filonov, Grigory S. (Curr Protoc Chem Biol, 2016)
RNA spatial dynamics play a crucial role in cell physiology and thus the ability to monitor RNA localization in live cells can provide insight into important biological problems. This article focuses on imaging RNAs using an “RNA mimic of GFP”. This approach relies on a RNA aptamer, called dimeric Broccoli, which binds to and switches on the fluorescence of DFHBI, a small molecule mimicking the fluorophore in GFP. Dimeric Broccoli is tagged to heterologously expressed RNAs and upon DFHBI binding the fluorescent signal of dimeric Broccoli reports the transcript’s localization in cells. This protocol describes the process of validating the fluorescence of dimeric Broccoli-labeled transcripts in vitro and in cells, flow cytometry analysis to determine overall fluorescence levels in cells, and fluorescence imaging in bacterial and mammalian cells. Overall, the current protocol should be useful for researchers seeking to image high abundance RNAs, such as transcribed off the T7 promoter in bacteria or off Pol III-dependent promoters in mammalian cells.